Classification of combined partial knee arthroplasty. (August 2019) - Garner, A.; van Arkel, R. J.; Cobb, J.
Abstract : Aims: There has been a recent resurgence in interest in combined partial knee arthroplasty (PKA) as an alternative to total knee arthroplasty (TKA). The varied terminology used to describe these procedures leads to confusion and ambiguity in communication between surgeons, allied health professionals, and patients. A standardized classification system is required for patient safety, accurate clinical record-keeping, clear communication, correct coding for appropriate remuneration, and joint registry data collection. Materials and Methods: An advanced PubMed search was conducted, using medical subject headings (MeSH) to identify terms and abbreviations used to describe knee arthroplasty procedures. The search related to TKA, unicompartmental (UKA), patellofemoral (PFA), and combined PKA procedures. Surveys were conducted of orthopaedic surgeons, trainees, and biomechanical engineers, who were asked which of the descriptive terms and abbreviations identified from the literature search they found most intuitive and appropriate to describe each procedure. The results were used to determine a popular consensus. Results: Survey participants preferred "bi-unicondylar arthroplasty" (Bi-UKA) to describe ipsilateral medial and lateral unicompartmental arthroplasty; "medial bi-compartmental arthroplasty" (BCA-M) to describe ipsilateral medial unicompartmental arthroplasty with patellofemoral arthroplasty; "lateral bi-compartmental arthroplasty" (BCA-L) to describe ipsilateral lateral unicompartmental arthroplasty with patellofemoral arthroplasty; and tri-compartmental arthroplasty (TCA) to describe ipsilateral patellofemoral and medial and lateral unicompartmental arthroplasties. "Combined partial knee arthroplasty" (CPKA) was the favoured umbrella term. Conclusion: We recommend bi-unicondylar arthroplasty (Bi-UKA), medial bicompartmental arthroplasty (BCA-M), lateral bicompartmental arthroplasty (BCA-L), and tricompartmental arthroplasty (TCA) as the preferred terms to classify CPKA procedures. Cite this article: Bone Joint J 2019;101-B:922–928.